2019
DOI: 10.4310/cag.2019.v27.n1.a6
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution by fractional mean curvature

Abstract: In this paper we study smooth solutions to a fractional mean curvature flow equation. We establish a comparison principle and consequences such as uniqueness and finite extinction time for compact solutions. We also establish evolutions equations for fractional geometric objects that in turn yield the preservation of certain quantities, such as the positivity of the fractional mean curvature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…Thus, we have shown that −(P 1 ∩ S) ⊆ P 3 ∩ S, up to negligible sets. Combining this with (22), we conclude the proof of (21). Also, we notice that H ∩ P 1 ∪ P 2 = ∅ and K ⊆ P 1 .…”
Section: The Nonlocal Curvature Of Perturbed Stripssupporting
confidence: 67%
See 2 more Smart Citations
“…Thus, we have shown that −(P 1 ∩ S) ⊆ P 3 ∩ S, up to negligible sets. Combining this with (22), we conclude the proof of (21). Also, we notice that H ∩ P 1 ∪ P 2 = ∅ and K ⊆ P 1 .…”
Section: The Nonlocal Curvature Of Perturbed Stripssupporting
confidence: 67%
“…Other recent contributions in the study of the fractional (and more general nonlocal) mean curvature flows are the articles [6,10,22]. In [6], the convergence of a class of threshold dynamics approximations to moving fronts was established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is finite for every R > 0 and also that lim R→+∞ c(R) = 0, see [8,16]. For the computation in the case of fractional kernels, see [18].…”
Section: Appendix a Viscosity Solutions And Geometric Barriersmentioning
confidence: 99%
“…We denote by B r the ball of center 0 and radius r > 0, and we let B r (x) = x + B r . Moreover, we recall that, by the scale invariance of fractional mean curvature, for all x r ∈ ∂B r there holds (see [19, Lemma 2])…”
mentioning
confidence: 99%